Ambiguidade em regras de negócio e seus efeitos na resiliência e resistência de equipes de tecnologia da informação - Silva Junior, Wanderley da (2020)
This study aims to assess the impact of ambiguity in business rules on resistance in information technology teams, in addition to the role of resilience to assist in change processes. Adapting business rules usually implies that the information technology (IT) team moves from the known to the unknown, especially if these business rules are not very well developed. In such circumstances, resilience has the potential to be a positive aspect in processes of change because in addition to helping to continue the workflow, it can present better ways of doing it. Changes involving information technology, ambiguous business rules, resistance and resilience are out of the current logic due to the factors that can influence such resistance and the forms of resilience that can be applied in processes involving the IT team. For this reason, in the case of changes related to business rules, an exploratory and quantitative measurement research is necessary due to ambiguities and possible poor formulation of business rules. The research was divided into two studies. Study 1 used the Fuzzy Analytic Hierarchy Process (FAHP) multicriteria decision method to classify the concepts relevant to resistance. Eight criteria were found, divided into two categories (intrinsic and extrinsic). Study 2 used the structural equation modeling method to test the three hypotheses proposed for the present research. Only hypothesis 2 (ambiguous business rules negatively influence the resilience of the IT team) did not obtain a significant result. This work contributes to the IT literature by exploring the relationship between ambiguity, resistance and resilience in IT teams.